Development of Divide‐and‐Conquer Density‐Functional Tight‐Binding Method for Theoretical Research on Li‐Ion Battery. Issue 4 (21st November 2018) - Chou, Chien‐Pin; Sakti, Aditya Wibawa; Nishimura, Yoshifumi; Nakai, Hiromi
Abstract: The density‐functional tight‐binding (DFTB) method is one of the useful quantum chemical methods, which provides a good balance between accuracy and computational efficiency. In this account, we reviewed the basis of the DFTB method, the linear‐scaling divide‐and‐conquer (DC) technique, as well as the parameterization process. We also provide some refinement, modifications, and extension of the existing parameters that can be applicable for lithium‐ion battery systems. The diffusion constants of common electrolyte molecules and LiTFSA salt in solution have been estimated using DC‐DFTB molecular dynamics simulation with our new parameters. The resulting diffusion constants have good agreement to the experimental diffusion constants. Abstract : The diffusion constants of common electrolyte molecules and LiTFSA salt in solution have been estimated using the divide‐and‐conquer density‐functional tight‐binding molecular dynamics simulation with refined and newly created extension of the popular 3ob DFTB parameters. The resulting diffusion constants of the electrolyte molecules and lithium ions have good agreement to the experimental diffusion constants.